Phase I/II study of bortezomib‐melphalan‐prednisolone for previously untreated Japanese patients with multiple myeloma - Ogawa, Yoshiaki (Cancer Sci, 2013)
This phase I/II study was conducted to evaluate the safety and efficacy of bortezomib‐melphalan‐prednisolone in Japanese patients with previously untreated multiple myeloma who are ineligible for hematopoietic stem cell transplantation. One hundred and one patients were enrolled, and 99 patients received up to nine 6‐week cycles of bortezomib (0.7/1.0/1.3 mg/m(2)) on days 1, 4, 8, 11, 22, 25, 29, and 32 in cycles 1–4 and on days 1, 8, 22, and 29 in cycles 5–9, with melphalan (9 mg/m(2)) and prednisolone (60 mg/m(2)) on days 1–4 of each cycle. The recommended dose was determined in the phase I portion, and the overall response rate and safety of bortezomib‐melphalan‐prednisolone at the recommended dose were assessed in the phase II portion. The recommended dose of bortezomib was determined to be 1.3 mg/m(2). Grade 3 or higher non‐hematological adverse events included diarrhea (12%) and peripheral neuropathy (10%); grade 4 hematological adverse events included lymphopenia (41%), neutropenia (30%), and thrombocytopenia (22%). Eleven patients had lung injury associated with bortezomib; two had grade 3 disease, and the other nine had grade 1 or 2 disease. Of the 86 patients treated with 1.3‐mg/m(2) bortezomib in phases I and II, the median number of treatment cycles was 4.5, and the overall response rate was 70% (95% confidence interval: 59–79%). Bortezomib‐melphalan‐prednisolone with 1.3‐mg/m(2) bortezomib was considered to be tolerable and effective in Japanese patients with previously untreated multiple myeloma. However, further investigation is needed to refine the administration schedule.